After the blast : the ecological recovery of Mount St. Helens - Wagner, Eric Loudon (University of Washington Press, 2020)
"How life bounces back from epic destruction On May 18, 1980, people all over the world watched with awe and horror as Mount St. Helens erupted in southwestern Washington. Fifty-seven people were killed, and hundreds of square miles of what had been lush forests and wild rivers were to all appearances destroyed. While most people thought of the eruption as a catastrophe, a small, ragtag team of ecologists did not. For them, the eruption of Mount St. Helens was the opportunity of a lifetime. Here was an unprecedented chance to test some of ecology's oldest and most august theories about how plants and animals recover from a massive disturbance. Ecologists thought they would have to wait years, or even decades, for life to return to the mountain. But when a forest scientist named Jerry Franklin helicoptered into the blast area a couple of weeks after the eruption, he found small plants bursting through the ash and animals skittering over the ground. Stunned, he realized he and his colleagues had been thinking of the volcano in completely the wrong way. Rather than being a dead zone, the mountain was very much alive. Mount St. Helens has been surprising ecologists ever since, and in After the Blast, Eric Wagner takes readers on a fascinating journey through the blast area and beyond. From fireweed to elk, the plants and animals Franklin saw would not just change how ecologists approached the eruption and its landscape, but also prompt them to think in new ways about how life responds in the face of seeming total devastation"--